Understanding trajectories of population decline across rural and urban Europe: A sequence analysis - Newsham, Niall; Rowe, Francisco (Population space and place, 2023)
Population decline is projected to become widespread in Europe, with the continental population set to reverse its longstanding trajectory of growth within the next 5 years. This represents unfamiliar demographic territory. Despite this, literature on decline remains sparse and our understanding porous. Particular epistemological deficiencies stem from a lack of both cross‐national and temporal analyses of population decline. This study seeks to address these gaps through the novel application of sequence and cluster analysis techniques to examine variations in population decline trajectories since 2000 in 696 subnational areas across 33 European territories. The methodology allows for a holistic understanding of decline trajectories capturing differences in the ordering, timing, magnitude and spatial structure of population decline. We identify a typology of population decline distinguishing seven distinct pathways to depopulation and chart their geographies. Results revealed differentiated pathways of depopulation in continental subregions, with consistent and rapid declines in the east, persistent but moderate declines in central Europe, accelerating declines in the south and decelerating population declines in the west. Results also revealed differentiated patterns of depopulation across the rural–urban continuum, with urban and populous areas experiencing a deceleration in population decline, while decline accelerates or stabilises in rural areas. Small‐ and mid‐sized areas displayed heterogeneous depopulation trajectories, highlighting the importance of local contextual factors in influencing trajectories of population decline.